Construction of Food Law Based on Rights Approach to Realize the Right to Food - Zazili, Ahmad; Bakri, Mochammad; Yuliati, Yuliati; Safa’at, Rachmad (Technium Social Sciences Journal, 2022)
Countries ratified the International Covenant On Economic, Social and Cultural Rights (ICESCR) have obligation to implementitation in national level. The purpose of this study is to construct a national food law based on a rights approach realize the right to adequate of food. The importance of this research is because Indonesian national food law is not in accordance with the standards and norms contained in the ICESCR. The research method used is normative legal research using a statutory approach, a philosophical approach and a conceptual approach. The research findings, firstly, the Indonesian national food law is oriented towards the food security paradigm so that it does not regulate rights and obligations in fulfilling the right to food. Second, the formation of a national food law in the future must emphasize the rights of the community and the obligations of the state in fulfilling the right to food, as well as special treatment for food vulnerable groups. Recommendation, the need for the Indonesian government to establish a Food Sovereignty Law in order to realize the right to adequate and adequate food.